Anti-Microbiota Vaccine Reduces Avian Malaria Infection Within Mosquito Vectors - Aželytė, Justė; Wu-Chuang, Alejandra; Žiegytė, Rita; Platonova, Elena; Mateos-Hernandez, Lourdes; Maye, Jennifer; Obregon, Dasiel; Palinauskas, Vaidas; Cabezas-Cruz, Alejandro (Frontiers in Immunology, 2022)
Animal and human pathogens that are transmitted by arthropods are a global concern, particularly those vectored by mosquitoes (e.g., Plasmodium spp. and dengue virus). Vector microbiota may hold the key to vector-borne pathogen control, as mounting evidence suggests that the contributions of the vector microbiota to vector physiology and pathogen life cycle are so relevant that vectorial capacity cannot be understood without considering microbial communities within the vectors. Anti-tick microbiota vaccines targeting commensal bacteria of the vector microbiota alter vector feeding, and modulate the taxonomic and functional profiles of vector microbiome, but their impact on vector-borne pathogen development within the vector has not been tested. In this study, we tested whether anti-microbiota vaccination in birds targeting Enterobacteriaceae within mosquito midguts modulates the mosquito microbiota, and disrupt Plasmodium relictum development in its natural vector Culex quinquefasciatus. Domestic canaries (Serinus canaria domestica) were experimentally infected with P. relictum and/or immunized with live vaccines containing different strains of Escherichia coli. Immunization of birds induced E. coli-specific antibodies. The midgut microbial communities of mosquitoes fed on Plasmodium-infected and/or E. coli-immunized birds were different from those of mosquitoes fed on control birds. Notably, mosquito midgut microbiota modulation was associated with a significant decrease in the occurrence of P. relictum oocysts and sporozoites in the midguts and salivary glands of C. quinquefasciatus, respectively. A significant reduction in the number of oocysts was also observed. These findings suggest that anti-microbiota vaccines can be used as a novel tool to control malaria transmission and potentially other vector-borne pathogens.